Diagnosing neonatal transphyseal fractures of the distal humerus. Issue 4 (27th March 2017) - Kay, Matthew; Simpkins, Carly; Shipman, Peter; Whitewood, Colin
Summary: A traumatic birth can cause significant upper limb injury; the presenting features are non‐specific and the differential diagnosis long. Transphyseal fractures of the distal humerus are a rare but clinically important birth injury. This injury has typical radiographic findings, which due to the un‐ossified nature of the distal humeral epiphysis can easily be misinterpreted. This article presents the radiographic appearance correlated with arthrography, ultrasound and MRI obtained from four cases of neonatal transphyseal fracture of the distal humerus. We hope that by demonstrating the appearances for each of these imaging techniques in relation to the underlying pathology will reduce errors of interpretation that may lead to inappropriate diagnosis and management of these children.